CHORIONIC VILLI OF HUMAN EMBRYOS, DIED OUT OF SPORADIC AND RECURRENT MISCARRIAGES: A LECTIN HISTOCHEMISTRY ANALYSIS - Zastavnyy, I.; Yashchenko, A.; Lutsyk, A.; Tkach, I. (World of Medicine and Biology, 2014)
9 tissue samples of chorionic villi of human embryos, died in the first trimester of pregnancy at 4-13 weeks in-utero were investigated. Two research groups were formed: the first - sporadic miscarriages, the second - recurrent miscarriages. Control group consisted of 5 chorionic villi tissue samples of human embryos obtained after artificial abortion of physiological pregnancies at respective gestational age accomplished due to women’s demand. Histological material was fixed in 4% neutral formalin solution. To study the general morphology the 5-7 µm thick sections were stained with hematoxylin and eosin. Hydrocarbon cell surface glycopolymers determinants of chorionic villi and their intracellular compartments were studied by lectin-peroxidase technique using lectins PNA, GNA, WGA and PFA. Viewing and photographing of histological samples was performed using a microscope “Swift Instruments International”, equipped with camera “Echoo-Imager 502 000” using computer program “TopView 3.2”. General morphological studies shown changes of the shape and structure of chorionic villi in the investigated samples, compared with the control. Based on lectin histochemical studies the different exhibition level of lectin receptors in the chorionic villi structural components of 4-13-week-old human embryos was observed. The highest expression of lectin receptors WGA, GNA and PFA detected in the study group of recurrent miscarriage, indicating a violation of biopolymers end-stage glycosylation due to excessive activation of glycosidases, compared with a group of sporadic miscarriage and control group.